2021
DOI: 10.1088/1757-899x/1208/1/012019
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties comparison of PLA, tough PLA and PC 3D printed materials with infill structure – Influence of infill pattern on tensile mechanical properties

Abstract: One of the advantages provided by fused deposition modelling (FDM) 3D printing technology is the manufacturing of product materials with infill structure, which provides advantages such as reduced production time, product weight and even the final price. In this paper, the tensile mechanical properties, tensile strength and elastic modulus, of PLA, Tough PLA and PC FDM 3D printed materials with the infill structure were analysed and compared. Also, the influence of infill pattern on tensile properties was anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The choice to use technical PLA was determined by the need to obtain greater mechanical resistance than that which would be obtained using non-technical PLA filaments. Furthermore, the technical filament showed less brittleness than standard PLA (Pandzic and Hodzic, 2021). The diameter of the filament is 2.85 ± 0.10 mm, with a density of 1.22 g/cm 3 .…”
Section: Methodsmentioning
confidence: 91%
“…The choice to use technical PLA was determined by the need to obtain greater mechanical resistance than that which would be obtained using non-technical PLA filaments. Furthermore, the technical filament showed less brittleness than standard PLA (Pandzic and Hodzic, 2021). The diameter of the filament is 2.85 ± 0.10 mm, with a density of 1.22 g/cm 3 .…”
Section: Methodsmentioning
confidence: 91%
“…Pandzic and Hodzic (2021) investigated the sample mechanical properties (tensile strength and elastic modulus) of PLA, tough PLA and PC materials using FDM technology with varying infill structure. The study results showed that infill pattern had a critical influence on tensile strength of the three selected materials.…”
Section: Study Backgroundmentioning
confidence: 99%
“…Accurately characterizing the electrical properties of 3D printed flexible materials is the first step to designing flexible hybrid electronics systems. Even materials of the same type from different manufacturers can exhibit variations in their dielectric properties due to differences in fabrication methods and material composition 15 . Thus, it is necessary to create a comprehensive library of common 3D printed flexible materials for different applications.…”
Section: Additively Manufactured Materials Characterizationsmentioning
confidence: 99%